Effect of Dry Needling Combined with Scapular Stabilization Exercises Versus Scapular Stabilization Exercises Alone in Rotator Cuff-related Shoulder Pain: A Randomized Controlled Trial - Syed Rais Akhter Rizvi (Journal of Advances in Medicine and Medical Research, 2026)
Background: Rotator cuff-related shoulder pain (RCRSP) is associated with pain, disability, and restricted shoulder function. Scapular stabilisation exercises are commonly used in rehabilitation, while dry needling may provide adjunctive pain modulation. Whether dry needling adds benefit to a structured scapular stabilisation programme remains uncertain. Objective: The study aims to compare dry needling combined with scapular stabilisation exercises with scapular stabilisation exercises alone in individuals with RCRSP. Methods: Thirty-six individuals were screened, and 32 eligible participants were randomised equally to two groups and completed the study. The experimental group received dry needling plus scapular stabilisation exercises, whereas the control group received the same exercise programme alone. Treatment was delivered three times weekly for four weeks. Pain, shoulder disability, and active shoulder range of motion were assessed at baseline and post-intervention using the Numeric Pain Rating Scale (NPRS), Shoulder Pain and Disability Index (SPADI), and goniometry. Results: NPRS decreased from 7.50 ± 1.63 to 2.94 ± 1.06 in the experimental group and from 7.50 ± 1.63 to 5.00 ± 1.26 in the control group. Mean reductions were 4.56 and 2.50 points, respectively, with a significant time × group interaction (F(1,30) = 73.30, p < 0.001). Both groups also improved in SPADI and all measured range-of-motion outcomes, with larger numerical changes in the experimental group. Internal rotation differed at baseline, warranting cautious interpretation. Conclusion: Both interventions improved clinical outcomes, while adding dry needling produced a greater short-term reduction in pain.